Who bears the burden of climate variability? A comparative analysis of the impact of weather conditions on inequality in Vietnam and Indonesia - Pacillo, Grazia; Cuong Nguyen Viet; Hafianti, Silvi; Abanokova, Kseniya; Hai-Anh Dang; Achicanoy Estrella, Harold Armando; Läderach, Peter R.D. (Agence Française de Développement, 2020)
Is climate variability regressive? One argument could be as follows: People living in areas with high risk of climate hazards usually correspond to the most disadvantaged populations. Due to existing structural inequalities, they have limited opportunities to cope with climate hazards and often fall into a spiral of further poverty and social exclusion. In this paper, we investigate whether climate variability indeed has a regressive effect in Vietnam and Indonesia where both climate variability and inequality have been increasing. We directly analyse the effect of annual and seasonal temperature on income and income inequality across years. We do so by looking at the Vietnamese and Indonesian populations as a whole and also investigating more in-depth how these impacts change for the most vulnerable and marginalised groups. Our results suggest that climate variability increases inequality and that its biggest burden is bore by existing vulnerable groups. In Indonesia, these groups are rural, farming, low educated, female headed households, whose income is significantly reduced because of changes in climate conditions. Similarly, in Vietnam, ethnic minorities, rural, farming, and agricultural households bear the biggest impact of climate variability. Interestingly, some households in Vietnam are able to completely offset short-term impact of climate variability, using remittances and transfer as an insurance, but our findings also show that their coping strategy does not withstand longer term impacts of persistent climate variability. Despite the remarkable efforts of the national governments in supporting most vulnerable and marginalised groups in the Vietnamese and Indonesian societies in the past decades, specific interventions are needed to address the needs of those who are still bearing the biggest burden of climate impacts to finally allow even the “last mile” groups to escape poverty and exclusion.